A national study of antibiotic use in Greek pediatric hematology oncology and bone marrow transplant units. Issue 1 (26th April 2022) - Mantadakis, Elpis; Kopsidas, Ioannis; Coffin, Susan; Dimitriou, Gabriel; Gkentzi, Despoina; Hatzipantelis, Emmanouel; Kaisari, Aikaterini; Kattamis, Antonis; Kourkouni, Eleni; Papachristidou, Smaragda; Papakonstantinou, Evgenia; Polychronopoulou, Sophia; et al.
Abstract: Objective: We surveyed antimicrobials used in Greek pediatric hematology–oncology (PHO) and bone marrow transplant (BMT) units before and after an intervention involving education regarding the 2017 clinical practice guidelines (CPG) for the management of febrile neutropenia in children with cancer and hematopoietic stem-cell transplant recipients. Design: Antibiotic prescribing practices were prospectively recorded between June 2016 and November 2017. Intervention: In December 2017, baseline data feedback was provided, and CPG education was provided. Prescribing practices were followed for one more year. For antibiotic stewardship, days of therapy, and length of therapy were calculated. Setting: Five of the 6 PHO units in Greece and the single pediatric BMT unit participated. Participants: Admitted children in each unit who received the first 15 new antibiotic courses each month. Results: Administration of ≥4 antibiotics simultaneously and administration of antibiotics with overlapping activity for ≥2 days were significantly more common in PHO units in general hospitals compared to children's hospitals. Use of at least 1 antifungal was recorded in ∼47% of the patients before and after the intervention. De-escalation and/or discontinuation of antibiotics on day 6 of initial treatment increased significantly from 43% to 53.5% (P = .032). Although the number of patients requiring intensive care support for sepsis did not change, a significant drop was noted in all-cause mortality (P = .008). Conclusions: We recorded the antibiotic prescribing practices in Greek PHO and BMT units, we achieved improved prescribing with a simple intervention, and we identified areas in need of improvement.